Individualization of Physical Education teaching at Faculty of Humanities and Social Sciences in Zagreb - Gošnik, Jelka (Array, 2010)
This paper problematizes the phenomenon of individualization of working in Physical Education teaching at higher education institutions as continuation of kinesiological education after compulsory schooling. Its actuality is observed under the humanistic education as a result of differentiation of overall human activities, as much as intellectual and cultural, and educational as well. In this way, individualization in kinesiological education assumes a managed process that is determined and conditioned by individual characteristics of each subject in the teaching and its ways of learning, as well as overall context of educational institutions in which teaching takes place. The paper places special emphasis on diversity in all aspects of the subject's personality as well as in approaches to teaching kinesiological contents as the assumption of individualization of Physical Education teaching. Since students enrolled on universities don't bring to teachers record of their work and progress in physical-health educational field, there is a need for existence of portfolios for all educational levels which would accurately determine capabilities, activities, participation in teaching, habits and knowledge of each student. Faculty of Humanities and Social Sciences in Zagreb by using survey methods collects data that are extremely useful in individualized approach to teaching kinesiological contents at the Faculty. Individualization of teaching is an actual reality, but also a complex subsystem of differentiated teaching which occupies an important place in the development of teaching practice and improvement of sport at higher education institutions.